Análise de fatores pessoais de risco para ocorrência e gravidade de síndrome do túnel do carpo - Kouyoumdjian, João Aris (2000)
Between September/98 and May/99, 210 symptomatic carpal tunnel syndrome (CTS) patients were studied. All had bilateral nerve conduction studies and none had been surgically treated. Peripheral neuropathy was excluded. Three groups were defined according to the severity of nerve conduction changes: mild = median distal sensory latency, wrist-index finger, 14 cm (P2), 3.7 to 4.4 ms or sensory median/ulnar difference ³ 0.50 ms or median palm latency ³ 2.3 ms; moderate = P2 ³ 4.5 ms; severe = unrecordable sensory nerve action potential at P2. All latencies were measured to the negative peak. Only the right hand was considered for this study (200 hands), regardless of the electrophysiological findings in the left hand. Another group of 320 subjects without any CTS symptomatology or any known systemic disorders was used as control. The mean age was 50.3 ± 10.8 years for the study group (87.6% female) and 47.3 ± 14.8 years old for the controls (89.1% female). Body mass index (BMI) was 28.4 ± 5.0 for the CTS group and 25.4 ± 4.7 for controls (p < 0.001). Right wrist index (WI) was 0.706 ± 0.041 for the CTS group and 0.689 ± 0.037 for controls (p < 0.001). Logistic regression analysis for risk of having CTS showed an adjusted odds ratio of 1.11 (95% CI 1.07-1.16) per unit increase for BMI and 1.11 (95% CI 1.05-1.16) per 0.01 increase for WI. An ordinal polychotomous logistic regression analysis of the relationship between these factors and the electrophysiological severity of CTS showed proportional odds ratios (mild to severe) of 1.20 (95% CI 1.00-1.30) for 5 years increase in age and 1.10 (95% CI, 1.00-1.20) for 0.01 increase in WI. Higher BMI did not increase the risk of severe CTS. The conclusions were: 1. The variables WI and BMI were higher in CTS cases (p < 0.001). 2. More severe nerve conduction abnormalities were associated with higher age and WI but not with higher BMI.